Impact of an Electronic Template on Documentation of Obesity in a Primary Care Clinic. (October 2016) - Thaker, Vidhu V.; Lee, Felix; Bottino, Clement J.; Perry, Cassandra L.; Holm, Ingrid A.; Hirschhorn, Joel N.; Osganian, Stavroula K.
Identification of obesity at well-child care (WCC) examinations is a step toward intervention. Studies have shown suboptimal documentation in primary care clinics that can improve with the use of electronic health records (EHRs). This study investigated the impact of a standardized EHR template on documentation of obesity at WCC visits and its impact on physician behavior. A cohort of 585 children with severe early onset obesity (body mass index >99th percentile, age <6 years) was identified with an electronic algorithm. Complete records of visit notes were reviewed to extract history taking, counseling, and recording of obesity at a WCC visit. Use of a standardized EHR template for WCC visits is associated with improvement in rates of documentation of obesity (47% vs 34%, P < .01), without interruption of workflow. Documentation of obesity in the chart improved nutritional (66% vs 44%, P < .001) and physical activity counseling (23% vs 9%, P < .001).